1) 0
2) 2
Пошаговое объяснение:
1) 0,5(2y - 1) - (0,5 - 0,2y) + 1 = 0
у - 0,5 - 0,5 + 0,2у + 1 = 0
у + 0,2у + 1 - 1 = 0
1,2у = 0
у = 0 : 1,2
у = 0
2) -4(5 - 2m) + 3(m - 4) = 6(2 - m) - 5m
-20 + 8m + 3m - 12 = 12 - 6m - 5m
8m + 3m + 6m + 5m = 12 + 12 + 20
22m = 44
m = 44 : 22
m = 2
1) 0
2) 2
Пошаговое объяснение:
1) 0,5(2y - 1) - (0,5 - 0,2y) + 1 = 0
у - 0,5 - 0,5 + 0,2у + 1 = 0
у + 0,2у + 1 - 1 = 0
1,2у = 0
у = 0 : 1,2
у = 0
2) -4(5 - 2m) + 3(m - 4) = 6(2 - m) - 5m
-20 + 8m + 3m - 12 = 12 - 6m - 5m
8m + 3m + 6m + 5m = 12 + 12 + 20
22m = 44
m = 44 : 22
m = 2